Dampak Penerapan Kebijakan Self Assessment Guru dalam Program Pengembangan Keprofesian Berkelanjutan (Pkb) di Tahun 2016 dan 2018 terhadap Hasil Uji Kompetensi Guru (Ukg) di Indonesia - Irmalita, Indri Astuti; Jasmina, Thia (Jurnal Kebijakan Ekonomi, 2021)
The Continuous Professional Development (CPD) program and Teacher Competency Test (TCT) have been national programs to enhance teachers' competency in Indonesia since 2012. In 2016, there was a change in the implementation of the CPD program where the teacher self assessment policy was applied as an instrument in alternative learning mode (various mode) of the CPD program. However, subsequently, in 2017-2018, its implementation was changed to only a face-to-face mode for all results of the teacher self assessment. The main objective of this study is to see how the change of the implementation of the teacher self assessment policy in the CPD program affects teacher competency test. This study applies a panel data logistic method with a sample being 5,759 teachers who consistently participated in the CPD program from 2016 to 2018.